ZEB1 is Negatively Correlated with E-Cadherin in Prostatic Anomaly Tissue - Sari Eka Pratiwi; Sri Nuryani Wahyuningrum; Rachmagreta Perdana Putri; Danarto Danarto; Didik Setyo Heriyanto; Nur Arfian; Sofia Mubarika Haryana; Indwiani Astuti (Cell and BioPharmaceutical Institute, 2022)
Background: Prostatic anomalies are common in tumor or infection condition. The enlargement of prostate gland affects the epithelial cell polarity that involves epithelial-mesenchymal transition (EMT). Transition into mesenchymal is mediated by transcription factor ZEB1 and E-cadherin protein. Upregulation of ZEB1 and loss of E-Cadherin expression were associated to proliferation and metastasis of malignancy cells. This study aims to describe the correlation of ZEB1 and E-cadherin expression in prostatic anomaly.Materials and method: Samples were Formalin Fixed Paraffin Embedded (FFPE) block consist of 8 block Benign Prostatic Hyperplasia (BPH), 6 blocks High Grade Prostatic Intraepithelial Neoplasia (HGPIN) and 6 blocks Prostate Carcinoma (PCA). The blocks then sliced into 5 sections to be prepared for RNA extraction procedures. ZEB1 and E-Cadherin expression was analyzed by semi-quantitative procedures using PCR and electrophoresis. Correlation between ZEB1 and E-Cadherin espression was analyzed using Spearman’s rank correlation.Results: Relative expression of ZEB1 and E-cadherin mRNA in each group of prostatic anomaly were not significantly different (p>0.05). ZEB1 and E-Cadherin mRNA expression showed a significant and moderate level of negative correlation (p<0.05; 0.40 < r < 0.59). Increasing of ZEB1 mRNA expression will be followed by decreasing of E-Cadherin mRNA expression.Conclusion: ZEB1 negatively correlates with E-cadherin due to EMT process in prostatic anomaly. High expression of ZEB1 induced down-regulation of E-cadherin and vise versa. Various studies can be developed, especially the development of targeted therapy against ZEB1 to suppress the EMT process by increasing the expression of E-cadherin.Keywords: epithelial-mesenchymal transition (EMT), ZEB1, E-Cadherin, BPH, HGPIN, PCA